Pelatihan Desain Media Pembelajaran Berbasis Aplikasi Powerpoint Interaktif bagi Guru di SDN Inpres 3 Talise Kota Palu - Wahyuni H Mailili; Hajerina Hajerina (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The purpose of this community service activity is to train on the develop teachers ability in creating interactive powerpoint as learning medium for teachers at SDN Inpres 3 Talise Palu City, Central Sulawesi province. The methods used include lecturing, discussing and practicing. The steps of this community service program are 1) The stage of preparing and developing training materials; 2) Training and ; 3) Mentoring the practice . The results of the implementation of the service show that there is an in crease in the ability of teachers at SDN Inpres 3 Talise in developing knowledge, comprehension, professionalism and creativity in designing interactive powerpoint as a medium for learning mathematics in elementary schools.